PENGARUH FAKTOR EKSPOSI PADA PEMERIKASAAN ABDOMEN TERHADAP KUALITAS RADIOGRAF DAN PAPARAN RADIASI MENGGUNAKAN COMPUTED RADIOGRAPHY - Fahmi, Arif; Firdausi, K. Sofjan; Setia Budi, Wahyu (BERKALA FISIKA, 2008)
It has been researched about the change of exposure factors in radiographic examination of abdomen to radiographic quality and radiation exposure using computed radiography. The change of exposure factors to radiographic quality is obtained by measurement of radiographic density, which transmitted to step wedges and phantom abdomen. The density difference of step wedge and abdomen at each change of exposure factors result in radiographic contrast. To obtain radiation dose for patients, it is accounted by analytic method. The affect of scattering rate dose is obtained by measurement of scattering exposure rate using survey meter with positioned 100 cm from the object. The result of experiment shows that change of exposure factors in radiographic examination of abdomen makes no significant difference between radiographic density and contrast; however, it has decreased the patient dose. Keywords: radiation exposure, radiographic density and contrast